Benchmarks for environmental impact of housing in Europe: Definition of archetypes and LCA of the residential building stock. (November 2018) - Lavagna, Monica; Baldassarri, Catia; Campioli, Andrea; Giorgi, Serena; Dalla Valle, Anna; Castellani, Valentina; Sala, Serenella
Abstract: This study describes the results of Life Cycle Assessment (LCA) applied to 24 statistically-based dwelling archetypes, representative of the EU housing stock in 2010. The aim is to quantify the average environmental impacts related to housing in Europe and to define reference values (baseline scenario) for policies development. The average environmental impacts have been calculated taking into consideration the number of dwellings (clustered per typology, year of construction and climate zone) related to each representative model. System boundaries include production, construction, use (energy and water consumption), maintenance/replacement, and end-of-life phases of each dwelling. The environmental life cycle impact assessment was carried out using the ILCD method. EU average annual environmental impact per person, per dwelling, and per m 2 were calculated. Results show that the average life cycle greenhouse gases emissions related to housing per person per year are 2.62 t CO2 eq and related to a representative dwelling per year are of 6.36 t CO2 eq. The use phase (energy and water consumption) is the most relevant one, followed by the production and the maintenance/replacement phases. Single-family houses are responsible for the highest share of impacts related to housing in Europe. The same type of building has different impacts in different climatic zones, due to the differences in the need for space heating. In general, electricity use and space heating are the activities that contribute more to the overall impacts. The final results could be used as a baseline scenario for testing eco-innovation scenarios and setting targets toward impact reduction. Highlights: The EU residential housing stock is modelled by means of 24 representative dwellings. A detailed LCA-based analysis of the environmental impact of housing in the EU is carried out. The impacts of all lifecycle stages are presented for 16 impact categories. The highest environmental impact is due to use phase and the production of materials. The impact of EU housing stock may represent a baseline for testing ecoinnovations scenarios.